Portable Pico Hydro Power Plant for Power Station Charger - Muhammad Taufiqurrohman; Dita Octaviani (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
The increasing need for energy will cause the depletion of energy reserves on earth and require energy reserves that can be renewed. Water flowing energy is the right choice to replace it by using it to generate electricity. And electrical energy can be stored in batteries that can be used at any time. In this study, converting the energy of the water into electricity is stored in batteries in the form of portable generators that can be taken anywhere. By requiring a component such as a turbine, generator, charger controller, auto buck bost converter, battery and other supporting components that are assembled into one in a portable form. With out a 12V battery that can increase and decrease the voltage as a charger for cellphones, laptops and other electronic equipment. By taking the results obtained, do a comparison by comparing the difference in the discharge of flowing water with the charging time on the power charger. The results obtained were river discharge 73.621 l/s charging time 42 hours, river discharge 73.621 l/s charging time 42 hours, pipe discharge 6.41 l/s charging time 84 hours, pipe discharge 8.064 l/s pipe charging time 38 hours, pipe discharge 9.868 l/s charging time 32 hours, pipe discharge 14.42 l/s pipe 27 hour. The greater the discharge,the faster the charging of the battery.